Ressignificâncias da paisagem no licenciamento ambiental - Renata Ribeiro Abreu Paranhos (2022)
The dissertation discusses the significance of landscape related to the Environmental License process, conformed to economic enterprises that need large territorial extensions for their operation, which cause significant impact. This research aims to discuss the environmental process, from a holistic and sensitive point of view, considering social and collective interests. We present recent Brazilian and international experiences that show large incidences in the local landscapes because of the economical activity. Mining activity cases were chosen due to their importance in Brazilian territory and especially in the state of Minas Gerais, as well as for the economic development, and social and cultural, relations, and legal apparatus. Its stimulant and degrading potential, however, lights an alert regarding the landscape significance, shedding light on ways to rethink environmental studies. Landscape thus emerges as a main indicator, indispensable tool, methodology to be worked on before, during and after the License.